More fruit diversity for food security - Sekandi, Eddie; Machida, Lewis; Carpentier, Sebastien (2024)
The overarching goal of the project is (i) to foster food and nutrient security especially in view of climate change, and (ii) to mitigate biodiversity loss and conserve the local diversity by filling the gaps in the local gene bank and the ITC collection in Leuven.